2011
DOI: 10.1121/1.3589254
|View full text |Cite
|
Sign up to set email alerts
|

Memory for the locations of environmental sounds

Abstract: The accuracy with which a single source of sound can be localized has been examined in many studies, but very few studies have examined the ability of participants to determine the absolute locations of multiple sources of sound. The current study assessed participants' abilities to determine and remember the locations of up to six sources of environmental sound that were positioned at a range of azimuths and elevations in virtual auditory space. In experiment 1, a sequence of one to six sounds was presented o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Note that in this study, the listeners' task involved focusing on all sound sources simultaneously rather than on one of them at a time as in the Brungart et al (2005) and Simpson et al (2007) studies. Martin et al (2011) presented listeners with up to six sources of environmental sounds positioned around the listener in an AVR space. The sequence of 1 to 6 sounds was presented 1, 3, or 5 times, and the target sound was revealed after the presentation of the last sequence.…”
Section: Localization Of Multiple Sound Sourcesmentioning
confidence: 99%
“…Note that in this study, the listeners' task involved focusing on all sound sources simultaneously rather than on one of them at a time as in the Brungart et al (2005) and Simpson et al (2007) studies. Martin et al (2011) presented listeners with up to six sources of environmental sounds positioned around the listener in an AVR space. The sequence of 1 to 6 sounds was presented 1, 3, or 5 times, and the target sound was revealed after the presentation of the last sequence.…”
Section: Localization Of Multiple Sound Sourcesmentioning
confidence: 99%
“…A set of HRIRs had been measured previously for each participant following the procedures described by Martin et al (2011). As described in the appendix, the fidelity of these HRIRs was evaluated and found to be satisfactory.…”
Section: Spatializationmentioning
confidence: 99%
“…Several previous studies have shown that target localization can be influenced by stimuli preceding the target on the time scale of seconds. These studies examined various phenomena and their underlying mechanisms, including adaptation of the neural representation due to prolonged exposure to preceding stimuli (Carlile et al, 2001;Dahmen et al, 2010;Furukawa, 2005;Kashino and Nishida, 1998;Phillips and Hall, 2005), attentional cuing (Maddox et al, 2014;Maier et al, 2010;Sach et al, 2000), buildup of the precedence effect (Freyman et al, 1991), auditory grouping (Best et al, 2007;Kopčo et al, 2017), spatial memory (Martin et al, 2011), and attentional effects utilizing a priori information about the position of the target and maskers (Kopčo et al, 2010). The current study examines which of these phenomena and their underlying mechanisms might be related to CP.…”
Section: Introductionmentioning
confidence: 99%